Konsep Ta’dib Menurut Pandangan Sarjana Pendidikan Islam [The Concept of the Ta’dib According to Islamic Educational Scholars] - Rahimah, Embong; Mior Mohd Mizan, Mior Pi; Kasimah, Kamaruddin; Firdaus Khairi, Abdul Kadir (2019)
Education inherited from the past until nowaday is Western-based education aimed at creating responsible citizens. However, Islam has promoted an education based on the concept of ta'dib a long time ago. Initially, ta'dib is the process of educating that mainly focuses on the formation and perfection of morals of Muslim personality. There are many different views related this concept of ta'dib among Islamic educational scholars such as al-Attas, Imam Al-Ghazali and Ibn Sina. This article will explore their background as well as their views regarding this educational concept of ta'dib.